Synthesis and Characterization of PANI/ZnFe2O4 nRs with Different Doping Concentrations for Potential Applications in Various Fields - Hamdalla, Taymour A.; Aljohani, Meshari M.; Alsharari, Abdulrhman M. (Journal of Spectroscopy, 2023)
The wide-ranging potential of polyaniline (PANI) composites in energy storage, electrochemical, sensing, and electromagnetic shielding applications emphasizes researchers to improve its properties. Here, the doping of ZnFe2O4 nRs by 1, 3, and 5 wt. % within polyaniline has been done. Then, we characterize the doped material using techniques such as scanning electron microscopy (SEM), X-ray diffraction (XRD), thermal gravimetric analysis (TGA), and Fourier-transform infrared spectroscopy (FTIR) to verify the successful incorporation of polyaniline onto the nRs. TGA showed that doping of PANI with ZnFe2O4 nRs enhanced the interfacial interactions between the two components. This provided a more stable matrix structure and enhanced the thermal stability of the composite. The transmission of light has been increased by about 18% due to the increase in crystallinity accompanied by ZnFe2O4 doping. As the ZnFe2O4 nRs doping rose, our PANI samples’ optical band gap values slightly decreased by about 10%. In addition, it has been found that the optical characteristics such as refractive index, extension coefficient, surface, and volume energy loss function essentially showed ZnFe2O4 doping dependency. The nonlinear constants of the doped samples have increased due to the new charge carriers and altered the electronic and optical properties of the composite material. Our obtained results show that PANI@ ZnFe2O4 nRs have potential applications such as optical sensors, electrochemical, optoelectronics, and photocatalysis.